Characterization and cytotoxicity evaluation of biocompatible amino acid esters used to convert salicylic acid into ionic liquids - Moshikur, R.M. (Elsevier B.V., 2018)
The technological utility of active pharmaceutical ingredients (APIs) is greatly enhanced when they are transformed into ionic liquids (ILs). API-ILs have better solubility, thermal stability, and the efficacy in topical delivery than solid or crystalline drugs. However, toxicological issue of API-ILs is the main challenge for their application in drug delivery. To address this issue, 11 amino acid esters (AAEs) were synthesized and investigated as biocompatible counter cations for the poorly water-soluble drug salicylic acid (Sal) to form Sal-ILs. The AAEs were characterized using 1H and 13C NMR, FTIR, elemental, and thermogravimetric analyses. The cytotoxicities of the AAE cations, Sal-ILs, and free Sal were investigated using mammalian cell lines (L929 and HeLa). The toxicities of the AAE cations greatly increased with inclusion of long alkyl chains, sulfur, and aromatic rings in the side groups of the cations. Ethyl esters of alanine, aspartic acid, and proline were selected as a low cytotoxic AAE. The cytotoxicities of the Sal-ILs drastically increased compared with the AAEs on incorporation of Sal into the cations, and were comparable to that of free Sal. Interestingly, the water miscibilities of the Sal-ILs were higher than that of free Sal, and the Sal-ILs were miscible with water at any ratio. A skin permeation study showed that the Sal-ILs penetrated through skin faster than the Sal sodium salt. These results suggest that AAEs could be used in biomedical applications to eliminate the use of traditional toxic solvents for transdermal delivery of poorly water-soluble drugs. Â© 2018 Elsevier B.V.